Prognostic relevance of urokinase plasminogen activator detection in micrometastatic cells in the bone marrow of patients with primary breast cancer - Solomayer, Erich-Franz; Diel, Ingo J.; Wallwiener, Diethelm; Bode, Simone; Meyberg-Solomayer, Gabriele Christine; Sillem, Martin; Gollan, Christina; Kramer, Michael D.; Krainick-Strobel, Ute Elisabeth; Bastert, Gunther (British journal of cancer, 1997)
Patients with an elevated level of urokinase plasminogen activator (uPA) in breast cancer tissue have an adverse prognosis. This study evaluated the prognostic relevance of uPA detection in disseminated tumour cells in bone marrow. Bone marrow was sampled intraoperatively from both iliac crests in 280 patients with primary breast cancer. Interphase cells were enhanced and stained immunocytologically with two antibodies: 2E11, which detects TAG 12--a tumour-associated glycoprotein typically expressed by almost all breast cancer cells--and the anti-uPA antibody HD-UK9. Thirty-five of the 2E11-positive women (n = 132, 47%) developed metastatic disease (median follow-up time 44 months). Of these, most were uPA positive (n = 23, 65%) and only 12 were uPA negative. Patients with uPA-positive cells in bone marrow (n = 98, 35%) had a significantly shorter metastasis-free interval (36 months) than women who were uPA negative (44.5 months). The worst prognosis was seen in patients positive for both markers (29.5 months), followed by those who were uPA negative and 2E11 positive (37 months). The detection of uPA on disseminated tumour cells characterizes a subgroup of patients with an even worse prognosis, who should undergo more aggressive adjuvant systemic therapy. For the first time, it was possible to evaluate an important qualitative parameter involved in the process of breast cancer metastases.